Growth and photochemical efficiency of Paulownia hybrid exposed to different water regimes - Subahi, Nursuhaili (2018)
Paulownia hybrid was a new introduced species for forest plantation and was still lacking in physiological data. As every state has received different amount of precipitation, water becomes major environmental variables where it can influence the physiological activity. The main objective of this research was to determine the effect of different level s of water regime on the growth, photochemical efficiency and efficiency growth of Paulownia hybrid. The plants were exposed to the treatment, which was different water regimes; low, medium and high. The growth and efficiency parameters of Paulownia hybrid such as height, diameter, leaf area and dry mass were taken. The measurements of chlorophyll fluorescence include the determination of initial fluorescence (Fo), maximal fluorescence (Fm), variable fluorescence (Fv) and photochemical efficiency (Fm/Fv). These data were analysed by using General Linear Model and analysis of variance (ANOVA) where treatment as a fixed factor. As a result, Paulownia hybrid gave a higher mean value in term of growth and biomass when exposed to high water regime rather than low and medium water regime. An efficiency growth (EG) of Paulownia hybrid when exposed to different water regimes did not had significant difference. However, low water regime had high mean value of EG compared to medium and high water regime. Paulownia hybrid showed similar pattern line of chlorophyll fluorescence within five second intervals by using Sigma Plot 14.0 software. Fv/Fm of all water regimes were not in range of 0.79 to 0.84, indicating that all the leaves were under stress. Therefore, Paulownia hybrid was affected by water regime in term of growth, biomass and photochemical efficiency but not in chlorophyll fluorescence.